The proactive brain and the fate of dead hypotheses - Tal, Amir; Bar, Moshe (Frontiers in Computational Neuroscience, 2014)
A substantial portion of information flow in the brain is directed top-down, from high processing areas downwards. Signals of this sort are regarded as conveying prior expectations, biasing the processing and eventual perception of incoming stimuli. In this perspective we describe a framework of top-down processing in the visual system in which predictions on the identity of objects in sight aid in their recognition. We focus, in particular, on a relatively uncharted ramification of this framework, that of the fate of initial predictions that are eventually rejected during the process of selection. The behavioral, neuronal and computational aspects of this process are discussed, and future directions for related research are proposed.